A magyar munkaerő-migráció regionális sajátosságairól - Àgnes Hárs (Hungarian Academy of Sciences, Institute of Economics, 2004)
– Migration is, in fact, regional mobility, movement from one geographical region to an other one. Various considerations suppose, there was a switch between unemployment and foreign labour, people in disadvantages labour market position or those who became unemployed search for foreign labour opportunity. Others underline the very limited internal labour mobility and make a correspondence with the international mobility. Wage gain is an evident, however not unique, motivation for migration. Are there additional regional peculiarities in labour emigration? The paper is based on the research of individual dataset of the legal labour emigrants into the EU countries in the year of 2001. In details will be analysed the recruitment of the migrants, the difference among the settlements they live, the labour market situation, ethnic differences, etc. According to evidences of the paper, emigration is aiming at German language countries; it is taking off from various parts of Hungary, mostly from settlements with medium or better off labour market situation. Various labour migration programmes follow various migration recruitment patterns. Skilled labourers are taking part successively in foreign labour; the share of settlements with high share of ethnic German population is high among seasonal worker; commuting over the Austrian border takes about the same time than that in Hungary is usual.
Keywords: 330; Arbeitsmigranten; Migranten; Ungarisch; Ungarn; EU-Staaten